Penerapan Algoritma Apostolico Crochemore Pada Perancangan Aplikasi Loundry Mobile Berbasis Android - Berkat, Feri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Laundry service is one of the service businesses engaged in washing clothes which incidentally is intended for the upper middle class, where they do not have time to wash their own clothes so they entrust their laundry to laundry services around them. The presence of laundry services in the lives of the general public has a positive impact by reducing activities outside of the many activities, both college activities and even work activities. Users of laundry services are usually found, from students to office workers, and others. Laundry services generally offer services for washing t-shirts, shirts, pants, blankets, bad covers, and others. Each laundry service provider generally provides different rates starting with a price of 5 thousand rupiah per kilo gram to 30 thousand rupiah per kilo gram depending on the quality offered by the laundry service provider. The existence of a price difference offered by laundry service providers, of course, consumers want to find a laundry service provider that is in accordance with financial conditions and the desired quality, this makes prospective laundry service users need to compare the price and quality provided by laundry services. To find information that contains information about the price and quality offered by laundry services, it is difficult to be easily reached by prospective users of existing laundry services due to the distance between each laundry service provider